Prevalence of Impostor Phenomena among Undergraduate Nursing Students - Chaudhary, Tulasi; Sapkota, Devi; Aryal , Neelu; Senturi , Rajani (International Journal of Silkroad Institute of Research and Training, 2025)
Background: The impostor phenomenon is a psychological condition that is characterized by persistent doubt concerning one’s abilities or accomplishments accompanied by the fear of being exposed as a fraud despite evidence of one’s ongoing success. The aim of the present study was to assess prevalence of Impostor Phenomenon among 193 undergraduate nursing students at selected nursing colleges (Bharatpur Hospital Nursing College (BHNC) and BP Koirala Memorial Cancer Hospital (BPKMCH)) in Chitwan, Nepal. Method: A descriptive cross sectional study on Impostor Phenomenon among undergraduate nursing students was conducted. The total enumerative sampling technique used to select the sample. The data collection was collected through self-administered questionnaire technique. The twenty statements of the Clance IP scale were used to measure IP. The data was analyzed in IBM SPSS version 25.0 for window and interpreted in terms of descriptive and inferential statistics, ANOVA test was conducted. Result: The study revealed that 23.6% had few impostor characteristics, 56.0% had moderate impostor experiences, 18.8% had frequent IP experiences and 1.6% had intense IP experiences. The majority of undergraduate nursing students have moderate IP experiences. IP is more common among academic year. As per ANOVA test, first year were to be significant influencing factor of high degree IP (p=0.001). Conclusion: Hence, there is a need to conduct an awareness program, and a self-confidence building program to increase the level of confidence in students to help them cope with the impostor phenomenon.